First day jitters - Danneberg, Julie, 1958-; Love, Judith DuFour (Watertown, Mass. : Charlesbridge, 2000)
Sarah is afraid to start at a new school, but both she and the reader are in for a surprise when she gets to her class.
Keywords: First day of school -- Fiction; Schools -- Fiction; Teachers -- Fiction